Polymorphisms in Rhesus Macaque Tetherin Are Associated with Differences in Acute Viremia in Simian Immunodeficiency Virus Δnef-Infected Animals - Janaka, Sanath Kumar (J Virol, 2018)
Tetherin (BST-2 or CD317) is an interferon-inducible transmembrane protein that inhibits virus release from infected cells. To determine the extent of sequence variation and the impact of polymorphisms in rhesus macaque tetherin on simian immunodeficiency virus (SIV) infection, tetherin alleles were sequenced from 146 rhesus macaques, including 68 animals infected with wild-type SIV(mac)239 and 47 animals infected with SIV(mac)239Δnef. Since Nef is the viral gene product of SIV that counteracts restriction by tetherin, these groups afford a comparison of the effects of tetherin polymorphisms on SIV strains that are, and are not, resistant to tetherin. We identified 15 alleles of rhesus macaque tetherin with dimorphic residues at 9 positions. The relationship between these alleles and plasma viral loads was compared during acute infection, prior to the onset of adaptive immunity. Acute viremia did not differ significantly among the wild-type SIV-infected animals; however, differences in acute viral loads were associated with polymorphisms in tetherin among the animals infected with SIVΔnef. In particular, polymorphisms at positions 43 and 111 (P(43) and H(111)) were associated with lower acute-phase viral loads for SIVΔnef infection. These observations reveal extensive polymorphism in rhesus macaque tetherin, maintained perhaps as a consequence of variability in the selective pressure of diverse viral pathogens, and identify tetherin alleles that may have an inherently greater capacity to restrict SIV replication in the absence of Nef. IMPORTANCE As a consequence of ongoing evolutionary conflict with viral pathogens, tetherin has accumulated numerous species-specific differences that represent important barriers to the transmission of viruses between species. This study reveals extensive polymorphism in rhesus macaque tetherin and identifies specific alleles that are associated with lower viral loads during the first few weeks after infection with nef-deleted SIV. These observations suggest that the variable selective pressure of viral pathogens, in addition to driving the diversification of tetherin among species, also operates within certain species to maintain sequence variation in tetherin.